Unusual presentation of arsenic poisoning in a case of celiac disease - Hasanato, Rana M. (Ann Saudi Med, 2015)
Arsenic poisoning may occur from sources other than drinking water such as rice, seafood, or insecticides. Symptoms and signs can be insidious, non-specific, atypical, and easily overlooked. We present a 39-year-old woman with celiac disease who was on gluten-free diet for 8 years and presented with diarrhea, headache, insomnia, loss of appetite, abnormal taste, and impaired short-term memory and concentration, but with no skin lesions. Arsenic concentration in her 24-hour urine was 682.77 μg/g creatinine (normal <15). She responded very well to chelation therapy with dimercaptosuccinic acid given orally and recovered within 2 weeks. The suspected source of arsenic poisoning was rice, as drinking contaminated ground water is not known in Saudi Arabia and she had not taken seafood. Therefore, arsenic poisoning should be suspected based on the meticulous medical history in cases of patients with celiac disease whose main food is rice and who present with unusual symptoms.